Tumor burden score predicts tumor recurrence of non-functional pancreatic neuroendocrine tumors after curative resection. Issue 8 (August 2020) - Dong, Ding-Hui; Zhang, Xu-Feng; Lopez-Aguiar, Alexandra G.; Poultsides, George; Makris, Eleftherios; Rocha, Flavio; Kanji, Zaheer; Weber, Sharon; Fisher, Alexander; Fields, Ryan; Krasnick, Bradley A.; Idrees, Kamran; et al.
Abstract: Background: To investigate the feasibility of Tumor Burden Score (TBS) to predict tumor recurrence following curative-intent resection of non-functional pancreatic neuroendocrine tumors (NF-pNETs). Method: The TBS cut-off values were determined by a statistical tool, X-tile. The influence of TBS on recurrence-free survival (RFS) was examined. Results: Among 842 NF-pNETs patients, there was an incremental worsening of RFS as the TBS increased (5-year RFS, low, medium, and high TBS: 92.0%, 73.3%, and 59.3%, respectively; P  < 0.001). TBS (AUC 0.74) out-performed both maximum tumor size (AUC 0.65) and number of tumors (AUC 0.5) to predict RFS (TBS vs. maximum tumor size, p  = 0.05; TBS vs. number of tumors, p  < 0.01). The impact of margin (low TBS: R0 80.4% vs. R1 71.9%, p  = 0.01 vs. medium TBS: R0 55.8% vs. R1 37.5%, p  = 0.67 vs. high TBS: R0 31.9% vs. R1 12.0%, p  = 0.11) and nodal (5-year RFS, low TBS: N0 94.9% vs. N1 68.4%, p  < 0.01 vs. medium TBS: N0 81.8% vs. N1 55.4%, p  < 0.01 vs. high TBS: N0 58.0% vs. N1 54.2%, p  = 0.15) status on 5-year RFS outcomes disappeared among patients who had higher TBS. Conclusions: TBS was strongly associated with risk of recurrence and outperformed both tumor size and number alone.